DIGITAL CONTENT CRIMES IN CRIMINAL LIABILITY - Hakiki, Azizul; Mufidah, Nuruz Zakiyatul; Kunarso, Kunarso; Setyawati, Natalia (jfpublisher, 2024)
The retransmission or plagiarism of digital content on online platforms infringes intellectual property rights, especially copyright, and violates provisions related to electronic information. These actions include modifying, duplicating, rebroadcasting, or concealing the authenticity of works such as videos, photos, and music, which damages the moral and economic rights of the creator. This research uses a normative method to examine the classification of criminal acts of plagiarism in the Copyright Law and the ITE Law and the criminal sanctions imposed, namely imprisonment or fines in accordance with applicable regulations. The act of duplicating and plagiarizing digital content such as photos, videos, music, and other works with digital tools or through other irresponsible people violates the Copyright Law and ITE Law, so it can be subject to criminal sanctions or fines. This offense is considered to be committed intentionally, detrimental to the creator morally and economically, and will be sanctioned in accordance with applicable legal provisions. The result showed that people or groups who commit digital content crimes, like duplicating or plagiarizing copyrighted works on digital platforms, will face criminal liability under the Copyright Law and Electronic Transaction Information Law. These intentional acts, often done for commercial gain, violate the creator’s moral and economic rights and may result in imprisonment or fines as outlined in the law.